Fingerprinting the Fractional Order Phase Transitions in AdS Black Holes - Chabab, Mohamed; Iraoui, Samir (Frontiers in Physics, 2021)
In this paper, we have extended and deepened the study on fractional order phase transition (FPT) of a charged AdS black hole performed in \cite{Ma:2019hvr}. We have carried out a detailed analysis of FPT for several AdS black hole prototypes: black hole surrounded by quintessence background, $5D$ Gauss-Bonnet, $D$ dimensional RN-AdS BH, and lastly Kerr black holes. We have shown that the $4/3$ order FPT at critical points obtained in \cite{Ma:2019hvr} still holds for the first three black holes systems, while for Kerr black holes, the fractional order is rather $1/3$. These results suggest two remarkable features: Firstly $4/3$ order phase transition can be assumed for asymptotically AdS black holes spherical solutions, secondly the fractional order is not universal and can be affected by the geometric symmetry.